(untitled) (World Bulletin of Public Health, 2025)
The authors analyzed the results of surgical treatment of 1929 patients with chronic calculous cholecystitis (CCC). The patients were divided into two groups: a comparison group (776 patients, 2016–2018) and a main group (1153 patients, 2019–2021). The comparison group included 75 patients with traditional cholecystectomy (TCE), 536 with laparoscopic cholecystectomy (LCE), and 165 with cholecystectomy through a miniaccess. The main group consisted of 76 patients with TCE, 715 with LCE, 362 with a modified minimally invasive access. The authors summarize that the modified method of cholecystectomy through a mini-access is a reliable alternative to laparoscopic cholecystectomy, especially in the presence of contraindications